Teacher training with digital media inclusion. The experience in the Social Sciences area of the Escuelas de Innovación program (2011-2015) from its protagonists’ voices (Praxis Educativa, 2022)
Public policies in teacher training devoted to digital inclusion have become relevant in the context of socio-technical transformations and situations related to connectivity and the use of digital media in education since the lockdown for Covid-19. In this scenario, it is essential to look into past experiences which took place during the development of the most important national program: Conectar Igualdad, in order to reflect upon and plan future formative policies. From the findings of a broader research which centered on public policies of teacher training with digital inclusion and the case of the Escuelas de Innovación program (2011-2015), this work analyzes the paths of the training team in the Social Sciences area from the voices of its members and those of the teachers participating in such training.
Keywords: teacher training; digital inclusion; Social Sciences; Escuelas de Innovación; Conectar Igualdad